The Effects of Internal Control System on the Revenue Performance of Uganda Revenue Authority - Annah Grace Ngabi (Uganda Christian University, 2025)
This study investigated the influence of internal control systems on the revenue performance of the Uganda Revenue Authority (URA) with specific reference to the Nakawa Branch in the Central Region of Kampala, Uganda. The study was guided by three main objectives: to quantify the effectiveness and adequacy of the internal control elements instituted at URA, to examine the linkage between internal controls and revenue performance, and to ascertain the challenges faced in maintaining effective internal control systems. A descriptive cross-sectional study design employing both qualitative and quantitative methods was utilized in a bid to understand the phenomenon clearly. The target group was 350 workers in major departments which form part of internal control systems and income generation, and 187 respondents were chosen through stratified random sampling for survey and purposive sampling for key informant interviews. The study confirmed that internal controls of URA are fairly effective with particular strength in control environment, information and communication systems, and control activities. These were put in place in order to enhance accountability, minimize leakages of revenue, and achieve timely and accurate reporting of revenue. The risk assessment and monitoring mechanisms were found to be effective but varied with perception by staff and, therefore, may represent areas for improvement. The study also listed some of the limitations to the application of internal controls, for example, limited financial resources, technological factors, lack of training, change resistance, and human resource constraints. In face of these constraints, the study found a strong positive relationship between effective internal control mechanisms and revenue performance, proof that strong control mechanisms bear much responsibility for financial stability and effectiveness in operations. According to the findings of the study, the study recommends that URA invest in modern computerized information systems, facilitate regular staff training programs, conduct regular monitoring and evaluation of internal controls, ensure sufficient resources, and employ measures to reduce resistance to change. Strengthening these areas will enhance the effectiveness of internal controls, facilitate ease of revenue risks, and in turn increase the revenue performance of URA. Keywords: Internal control systems, revenue performance, Uganda Revenue Authority, control environment, risk assessment, monitoring, information systems
Undergraduate research